FINANCIAL STRATEGY AS A KEY TO BUSINESS SUSTAINABILITY - Ahmad Talib; Nekky Rahmiyati; Titiek Rachmawati (Adisam Publisher, 2024)
Good financial strategy is the key to sustainability in business. By carefully planning, managing and monitoring finances, businesses can secure their future and grow sustainably. In managing business financial strategies to achieve long-term success, there are several important strategies that need to be considered. A key component of managing the sustainability of an organization is financial strategy. Financial strategy and the organization have a number of interactions that should be taken into account. These relationships include managing stakeholder relationships, making investment decisions, controlling costs, tax planning, and the impact of financial decisions on the performance and value of the business. Businesses can cut wasteful expenses and boost revenues by controlling costs well. In this article, the researcher examines the method in the form of library research, namely research in its implementation by reviewing reading various literary sources, such as books related to financial strategy as the key to business sustainability, journals that have been searched for, and other articles for additional data sources. This research discusses the definition of financial strategy, factors that influence business sustainability, the role of financial strategy in achieving business sustainability, and the relationship between financial strategy and business sustainability.